A fatal case of aconite poisoning: accidental intake of a monkshood extract - Hofmann, Vanessa; Landmann, Aysche; Schmitt, Georg; Krauskopf, Astrid; Bartel, Marc (Forensic toxicology, 2020)
Monkshood is a wild growing plant which contains the very toxic alkaloid aconitine, and is often used in traditional Chinese medicine. In this case report, we describe a fatal accident after the unintentional consumption of an aconite extract.
Gesehen am 09.09.2021